Pelaksanaan Kurikulum Pendidikan Islam dan Berbagai Problematikanya - Salsabila Nahdiaturrosidah; Agus Zaenul Fitri; Abd. Aziz (STIKes Ibnu Sina Ajibarang, 2025)
Islamic education aims to shape a complete Muslim personality, develop human potential, and foster harmonious relationships between humans and Allah, among humans, and with the universe. The Islamic education curriculum is designed to integrate religious, academic, and practical aspects to produce graduates who are intellectually smart and rich in Islamic values. However, in its implementation, the Islamic education curriculum faces various challenges and issues. These include discrepancies between curriculum design and reality on the ground, lack of readiness in human resources and infrastructure, as well as the demands of globalization and rapid technological development. Additionally, there is an imbalance between theoretical and practical aspects in the curriculum, and challenges in balancing local needs with global demands. This research aims to present the problems in the implementation of the Islamic education curriculum and its evaluation. The method used in this research is a qualitative approach using literature review. The results of this research show that the implementation of the Islamic education curriculum in Indonesia still faces various challenges that require serious attention. The availability and quality of teachers, curriculum standardization, facilities and infrastructure, teaching methods, and technology integration are aspects that need improvement. With comprehensive evaluation and the implementation of appropriate recommendations, it is expected that the Islamic education curriculum can be more effective and produce a generation that is both qualified and of noble character.